Comparison of Dental Prostheses Cast and Sintered by SLM from Co-Cr-Mo-W Alloy - Myszka D.; Skrodzki M. (Archives of Foundry Engineering, 2016)
The article presents the results of a comparative analysis of the metal substructure for dental prosthesis made from a Co-Cr-Mo-W alloy by two techniques, i.e. precision investment casting and selective laser melting (SLM). It was found that the roughness of the raw surface of the SLM sinter is higher than the roughness of the cast surface, which is compensated by the process of blast cleaning during metal preparation for the application of a layer of porcelain. Castings have a dendritic structure, while SLM sinters are characterized by a compact, fine-grain microstructure of the hardness higher by about 100 HV units. High performance and high costs of implementation the SLM technology are the cause to use it for the purpose of many dental manufacturers under outsourcing rules. The result is a reduction in manufacturing costs of the product associated with dental work time necessary to scan, designing and treatment of sinter compared with the time needed to develop a substructure in wax, absorption in the refractory mass, casting, sand blasting and finishing. As a result of market competition and low cost of materials, sinter costs decrease which brings the total costs related to the construction unit making using the traditional method of casting, at far less commitment of time and greater predictability and consistent sinter quality.